The STREK project - Sist, P.; Bertault, J.G. (1997)
STREK is the acronym for Silvicultural Techniques for the Regeneration of logged over forests in East Kalimantan, Indonesia project. The Ministry of Forestry of Indonesia and CIRAD-Forìt were the lead the institutions. The Indonesian state-owned company INHUTANI I was the implementation agency in the field. The study area located in the Indonesian province of East Kalimantan. The INHUTANI I concession was mainly covered by primary and logged lowland mixed dipterocarps forest. Two sites, 1000 ha each, were selected. On the first site (RKL 1), logged in 1978-1979, six plots, 4 ha each were set up. On the second site (RKL 4), covered by primary forst until 1991, 12 plots, 4 ha each were set up. The plots, all trees with dbh = 10 cm were measured, numbered and mapped on a scale of 1:200. Other important physical features such as topography and soil were also assessed in each plot. Two different silvicultural treatments (chemical thinning) were tested in RKL 1. Reduced-impact logging techniques (RIL) were applied and compared to conventional ones in RKL 4. Four treatments were defined: two RIL, with two different diameter limits (>50 and >60 cm), one conventional and a control without harvesting. Reduced -impact logging techniques included planning of skid-trails before logging, directional felling, and climber cutting three months before logging.